Explicación paso a paso:
[tex] x_1 = \frac{ - ( - 5) + \sqrt{( - 5) ^{2} - 4( - 3)(2)} }{2( - 3)} \\ = \frac{5 + \sqrt{1} }{ - 6} = - 1[/tex]
[tex]x_2 = \frac{ - ( - 5) - \sqrt{( - 5) ^{2} - 4( - 3)(2)} }{2( - 3)} \\ = \frac{5 - \sqrt{1} }{ - 6} = - \frac{2}{3} [/tex]
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Explicación paso a paso:
[tex] x_1 = \frac{ - ( - 5) + \sqrt{( - 5) ^{2} - 4( - 3)(2)} }{2( - 3)} \\ = \frac{5 + \sqrt{1} }{ - 6} = - 1[/tex]
[tex]x_2 = \frac{ - ( - 5) - \sqrt{( - 5) ^{2} - 4( - 3)(2)} }{2( - 3)} \\ = \frac{5 - \sqrt{1} }{ - 6} = - \frac{2}{3} [/tex]